تکثیری معاشرے میں مذہبی و سماجی تنازعات کے حل کا نبوی منہج:پاکستانی تناظر میں تجزیاتی مطالعہ: Prophetic Approach in Solving Socio-Religious Conflicts in a Plural Society: An Analytical Study in Pakistani Context - Dr. Riaz Ahmad Saeed,; Masood Akram, (MEI, 2025)
Socio-religious and socio-political conflicts are the part of our societal life, which sometimes becomes very challenging task to resolve them even in the modern era too. However, if these conflicts are not resolved in a sensible and deliberate manner, these conflicts can seriously disturb the peace and prosperity of the society and may cause a harmful condition. In the early history of Islam, there were conflicts and confrontations with polytheists, Jews, and Christians in Makkah and Madīnah. A significant part from the life of the Prophet Muhammad (PBUH) was spent in resolving these problems, so they shed light about this aspect of the Prophet's life, how to resolve conflicts and how to make society peaceful. Especially, when the Holy Prophet (PBUH) reached Madīnah, he came into contact with a diverse and multicultural society and state. Being the chief executive of the state, the Prophet of Allah laid down some principals of the state and society, which were Justice, equality, public security, accountability, consultation, economic welfare, and protection of ethical aspect of the public. Muslims and People of the Book (Jews and Christians) were two major parties in this state, while polytheists and hypocrites were also present in a reasonable number. In this context, this study defines the strategy of the Prophet (PBUH) that was adopted to resolve inter-religious conflicts in the state of Madīnah. Even in this modern age, many conflicts are arising on religious, political, and ethnic grounds. Despite being a Muslim majority country, Pakistan is a multi-ethnic and multi-religious society in which such incidents are natural. Analytical method of research has been adopted in this research to reach the results. Based on the available sources, this paper perceives that dialogue, peaceful co-existence, respect, tolerance, peace agreements, ceasefire, peace, and amnesty were adopted by the Prophet Muhammad (PBUH) as strategies to resolve conflicts. Therefore, this study suggests that the socio-religious disputes and conflicts can be resolved in the light of principles of the Prophet's (PBUH) Sīrah in contemporary multicultural societies.